Automatic Control of Contextual Interaction Integrated with Affection and Architectural Attentional Control. (14th March 2013) - Jiang, Yanrong; Xiao, Nanfeng; Han, Jianhua
It is still a challenge for robots to interact with complex environments in a smooth and natural manner. The robot should be aware of its surroundings and inner status to make decisions accordingly and appropriately. Contexts benefit the interaction a lot, such as avoiding frequent interruptions (e.g., the explicit inputting requests) and thus are essential for interaction. Other challenges, such as shifting attentional focus to a more important stimulus, etc., are also crucial in interaction control. This paper presents a hybrid automatic control approach for interaction, as well as its integration, with these multiple important factors, aiming at performing natural, human-like interactions in robots. In particular, a novel approach of architectural attentional control, based on affection is presented, which attempts to shift the attentional focus in a natural manner. Context-aware computing is combined with interaction to endow the robot with proactive abilities. The long-term interaction control approaches are described. Emotion and personality are introduced into the interaction and their influence mechanism on interaction is explored. We implemented the proposal in an interactive head robot (IHR) and the experimental results indicate the effectiveness.